The K469E genetic variant in the ICAM1 gene is associated with type 2 diabetes but not with its vascular complications: a meta-analysis - Saikrishna Lakkakula; Henu Kumar Verma; Bhaskar V.K.S. Lakkakula (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Type 2 diabetes mellitus (T2DM) is a metabolic disease characterized by diminished insulin secretion and hyperglycemia leading to damage of multiple organs. The present study is aimed to test the association between type 2 diabetes vascular complications and K469E variant (rs5498) of the intercellular adhesion molecule-1 (ICAM1) gene. Methods: Online databases were searched to retrieve all publications relating to the ICAM1 rs5498 variant in human diabetic vascular complications. In the present meta-analysis, we included all eligible studies and calculated the pooled results using MetaGenyo web tool. Results: Studies concerning ICAM1 gene K469E variant association with either type 2 diabetes or diabetes related vascular complications were included in this meta-analysis. Fifteen articles were included in this analysis (n=10 for T2DM; n=5 for diabetes nephropathy; n=8 for diabetes retinopathy). ICAM1 K469E variant significantly increased the risk of T2DM in the allelic (OR = 1.10, 95% CI: 1.01-1.20, P = 0.032) and recessive models (OR = 1.27, 95% CI: 1.08-1.49, P = 0.004). However, the ICAM1 gene K469E variant is not associated with diabetic nephropathy or diabetic retinopathy. No noticeable evidence of publication bias was detected. Conclusion: In summary, our study indicated that ICAM1 K469E variant was significantly associated with the increased risk of diabetes but not with the diabetic vascular complications.